Analysis of Air Heater Usage With Steam Heat Source Extracted From Turbine Against Fuel Savings Recovery Boilers - Frans Ferdinand Situmorang (International Journal of Mechanical Computational and Manufacturing Research, 2021)
Electricity is one of the biggest needs in Indonesia, especially in the fields of industry, therefore, every industry should be able to meet its own electricity needs. One company that can meet the needs of industry's own electricity is PT. Toba Pulp Lestari Tbk. The need for electricity met by operating two units of thermal power generation is Multifuel Boiler and Recovery Boiler. Recovery Boiler is a unit Boiler special used to purify compounds-chemical compounds inorganic contained in Black Liquor (waste cooking of the digester) as well as a steam generator of high pressure (High Pressure Steam. There are also some of the factors supporting the recovery boiler including: soot Blowing system, Medium Pressure steam, Low Pressure steam, Condensate, Electrostatic Precipitator (ESP). the air flow system in the recovery boiler which air enters through secondary air fan to the water heater, in the water heater outside air is heated using steam results from the extraction of the turbine, while to heat the steam into steam superheat before entering to turbine used flue gas originating from the combustion of fuel supplied to the superheater 2, superheater 1, and economizer is further from the economizer flue gas directly in the exhaust into the atmosphere through the chimney. In this study, obtained the heat absorbed water heater is equal to 7,525,904 kJ/ hour. The heat absorbed from the water heater ANSYS analysis calculations amounted to 9,854,555.38 kJ/h and fuel savings after using the tool air heating (air heater) is approximately 883 liters / hour. The fuel savings after using the tool air heating (air heater) from ANSYS analysis calculation is equal to 1,115 liters / hour. And to the calorific value which absorbed components in the boiler can be a data-data following data: HTS heat energy absorbed by 11,633,444 kJ/ hour, the heat energy absorbed by LTS 15,740,779 kJ / h and heat energy absorbed Economizer amounting to 21,516,347 kJ / h.